SWOT Analysis of Sustainable Tourism Development in Tetebatu, East Lombok - Siti Hamdiah Rojabi; Mahmudah Budiatiningsih; Aryan Agus Pratama (Faculty of Economics and Business, University of Mataram, 2023)
Tete Batu is one of the tourist villages in East Lombok Regency that offers tourist attractions of natural beauty, culture, and local traditions that have developed and are expected to be able to become sustainable activities. However, in its implementation, tourism development can also pose challenges related to sustainable tourism development from various aspects, such as community involvement, economic progress, socio-cultural sustainability, and environmental conservation efforts. This research aims to examine the development of sustainable tourism in Tete Batu by analyzing the potential of sustainable tourism in Tete Batu using SWOT analysis to identify the strengths, weaknesses, opportunities, and challenges faced in realizing sustainable tourism in this region. The results of this study found that there are strengths, and weaknesses internally as well as the existence of opportunities and threats in the development of tourism in Tete Batu, especially in the awareness and involvement of local communities and how to maintain the surrounding environment, so that efforts are needed to increase awareness and involvement as well as the ability of the community as human resources who are directly involved in tourism activities, besides that a comprehensive policy is needed related to efforts to preserve the environment and the lifestyle of local people in maintaining the surrounding environment both in terms of cleanliness and hygiene. This research is expected to be a reference for implementation recommendations or policies in tourism activities to maximize the benefits of sustainable tourism development for the community, managers, and government as a policy regulator.